Negotiating the Online Classes in Primary School in Indonesia - Bertiani Eka Sukaca; Benjarut Prempiwong (Universitas Sarjanawiyata Tamansiswa, 2020)
Running online classes for grade 1 of primary school in suburban in Indonesia has become a big challenge for teacher. On one hand, teacher has to reach a target of making the students achieve specific competencies as on the national curriculum 2013. On the other hand, different level of students’ skills, and internet credit expanses are two most cases required to be concerned. After doing the second treatment on 28 students of State Primary School 2 Bogem, Kalasan, the researcher found that the appropriate media used were WhatsApp and printed assignments. The teacher conducted WhatsApp classes twice a week and sent printed assignments every fortnight. Through these two media, the parents’ companion on the students’ learning process is getting optimum.